Factors affecting participation in the colorectal cancer screening program: a cross-sectional population study - Romanová, Alexandra; Lustigová, Michala; Urbanová, Jana; Keil, Radan; Krollová, Pavlína; Šťovíček, Jan; Wasserbauer, Martin; Hlava, Štěpán; Malinovská, Jana; Drábek, Jiří; Brož, Jan (Journal of cancer research and clinical oncology, 2023)
PURPOSE: Fecal immunochemical test (FIT) once a year or colonoscopy once in 10 years is the option approved for colorectal cancer (CRC) screening for asymptomatic individuals aged ≥ 50 years in the Czech Republic. We analyzed participation in the screening program to determine possible improvements. METHODS: In this observational cross-sectional study, data were collected from 4044 randomly chosen individuals from the Czech population (1866 men, 2178 women) aged ≥ 50 years by questionnaires. Individuals who underwent colonoscopy within the last 10 years or/and FIT within the last 2 years were classified as participants in the screening. RESULTS: 1050 individuals underwent FIT, 464 colonoscopy, and 558 underwent both. Adjusted for age, gender, and education, a higher chance of participation in the screening was observed in groups of non-smokers (OR = 1.25; CI 1.05-1.48), ex-smokers (OR = 1.51; CI 1.26-1.83), consuming smoked meat products less than once a week (OR = 1.26; CI 1.09-1.45), practicing physical activity at least once a week (OR = 1.25; CI 1.03-1.51), hospitalized in the past 12 months (OR = 1.73; CI 1.47-2.05), or consulting a general practitioner (GP) in the past 12 months (OR = 2.26; CI 1.87-2.74). The chance of participation of individuals having a risk factor for CRC (obesity, smoking, diabetes, low physical activity, alcohol drinking) was not higher compared to those without the risk factors. CONCLUSION: Individuals with a tendency to a healthy lifestyle or being in recent contact with the healthcare system by various means, mainly visiting a GP, had a higher participation in the screening for CRC. Among groups with an increased risk for CRC, higher participation was not shown.
Keywords: Diabetes; Colonoscopy; Mass Screening; Screening; Colorectal Neoplasms; Cross-Sectional Studies; kolonoskopie; rizikové faktory; průřezové studie; ženské pohlaví; časná detekce nádoru; lidé; Obesity; mužské pohlaví; Early Detection of Cancer; Physical activity; Risk Factors; Humans; Smoking; plošný screening; Female; kolorektální nádory; Alcohol drinking; Male